Pengaruh Temperatur Pencampuran Terhadap Campuran AC-BC Dengan Menggunakan Batu Sungai Seriti - Nobertus Pasambo; Alpius; Louise Elizabeth Radjawane (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
In the pavement layer temperature is very important in influencing the strength of the mixture on the asphalt. So if an asphalt mixture is not at the specified temperature, the bonds between the aggregates are reduced and will make the mixture weak. In this study, the intent and purpose was to test the mixing temperature of the AC-BC mixture using 5% asphalt. The methodology in this paper is the design of the AC-BC combination composition and also the Marshall immersion test in order to obtain the Marshall Residual Stability (SMS) value. From the research that has been done, it is obtained that the AC-BC mixture values in variations with mixing temperatures are 120℃, 130℃, 140℃, 150℃, and 160℃ with the value of Stability 1373.40, Flow 2.40 mm, VIM 3.46 %, VMA 15.27 %, FVB 77.33 %. Through a series of studies that have been carried out, it is concluded that the temperature in a mixture greatly affects the Marshall parameter value.